Une atmosphère très particulière - Caterina Guenzi (Revue d’Histoire des Sciences Humaines)
This contribution focuses on the efforts of contextualisation pursued by specialists of a discipline derived from Sanskrit literature and practised today in India, called vāstuśāstra, vāstuvidyā or vāstu, the “science of habitat”. Combining notions and techniques informed by architecture, iconography, ritual and divination, vāstu is today taught in several Indian universities and enjoys great popularity among the urban middle classes. By combining the study of textual sources and ethnographic materials gathered in the cities of Delhi and Benares, this article indicates the diversity of contextualisation efforts mobilised by the discipline’s specialists. “Sensitivity to context” can thus be viewed not only as an intellectual approach within an investigatory process, but also as a property of living beings reacting to the physical and sensory action of certain external agents, these two dimensions being closely linked.